2006
DOI: 10.1016/j.otohns.2005.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectations and Recovery Following Endoscopic Sinus Surgery

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Certainly, identifying patient variables and procedures associated with increased discomfort would allow for selective opioid prescribing practices, as suggested by this study and others. 3,4,6,7,14,17 The importance of preoperative counseling should also be emphasized, as it may provide concordance between patient expectation and realistic FESS postoperative course to help minimize opioid use. 4 Furthermore, individual surgeons can assess opioid requirements in their patient population and modify their own prescribing patterns accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, identifying patient variables and procedures associated with increased discomfort would allow for selective opioid prescribing practices, as suggested by this study and others. 3,4,6,7,14,17 The importance of preoperative counseling should also be emphasized, as it may provide concordance between patient expectation and realistic FESS postoperative course to help minimize opioid use. 4 Furthermore, individual surgeons can assess opioid requirements in their patient population and modify their own prescribing patterns accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 7% of patients in this study admitted to regularly using opioids prior to the procedure. 4 Svider and colleagues performed a systematic review of nonopioid treatment options following FESS using the Cochrane bias tool and Grading of Recommendations Assessment, Development and Evaluation criteria, and found that acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), and gabapentin were effective opioid alternatives. 5 Despite these findings, the number of narcotics prescribed remains relatively high and inconsistent between providers.…”
Section: Introductionmentioning
confidence: 99%
“…This can also be a source of significant anxiety and may negatively impact the patient's sense of overall recovery. 18 Various absorbable materials have been introduced to overcome the disadvantages of removable nasal packing or no packing. The ideal materials should be effective in immediate and prolonged hemostasis, have no detrimental effect on wound healing, and be absorbable and comfortable for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirms earlier reports showing that patients with ESS experience significant pain after surgery, which prevents the return to normal daily activities and thus these patients need to be provided with appropriate analgesic care. Chidambaram et al 4 and Mehta et al 14 have shown that most patients recover within 2 weeks after ESS. However, the present study indicates that with sufficient pain management, recovery may be accelerated by some days.…”
Section: Discussionmentioning
confidence: 99%